THE OBJECT OF THE CRIMINAL OFFENSE AND ITS STRUCTURE (ART. 180 OF THE CRIMINAL CODE OF UKRAINE) - Kovtun, Oleksii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to conduct a comprehensive analysis of the objects of criminal offenses, the legal compositions of which are provided for in the dispositions of art. 180 of the Criminal Code of Ukraine, taking into account the provisions of the theory of criminal law. Methods: deduction, formal-legal, logical-legal, cognitive-analytical, comparative-legal analysis and others. Results: taking into account a comprehensive analysis of the issue, the article analyzes both the object of the criminal offense in general and the objects of criminal offenses of specific crimes, the legal compositions of which are provided for in the dispositions "Obstruction of the implementation of a religious rite" art. 180 of the Criminal Code of Ukraine. The proposed solution of some important debatable issues, in particular, attention is paid to the issues of the general structure of the studied article of the Criminal Code of Ukraine of the Special Part of the Criminal Code of Ukraine, the definition and structure of objects of crimes. Discussion: considered modern concepts of the object of criminal offense. The article analyzes the general object of criminal offenses, the generic object of criminal offenses against electoral, labor and other personal rights and freedoms of man and citizen, specific and direct objects of criminal offenses, the legal compositions of which are provided for in the dispositions of art. 180 of the Criminal Code of Ukraine. In the theory of criminal law of Ukraine, there is a four-stage and three-stage classification of objects of criminal offenses. The four-stage classification of the object of a criminal offense more clearly reflects the common features of homogeneous criminal offenses, which, in particular, are contained in Chapter V of the Criminal Code of Ukraine. The structure of the object of criminal offense as a general phenomenon of criminal law, as well as the direct objects of crimes, the legal compositions of which are provided for in the dispositions of art. 180 of the Criminal Code of Ukraine. In particular, the direct main and additional objects of crimes, signs of victims of crimes and the non-objective nature of the crimes contained in art. 180 of the Criminal Code of Ukraine.